Diabetic Bone Disease and Diabetic Myopathy: Manifestations of the Impaired Muscle-Bone Unit in Type 1 Diabetes - Callie Travis; Priya S. Srivastava; Thomas J. Hawke; Evangelia Kalaitzoglou (Journal of Diabetes Research)
Type 1 diabetes is associated with complications affecting muscle and bone, with diabetic bone disease and diabetic myopathy becoming increasingly reported in the past few decades. This review is aimed at succinctly reviewing the literature on the current knowledge regarding these increasingly identified and possibly interconnected complications on the musculoskeletal system. Furthermore, this review summarizes several nonmechanical factors that could be mediating the development and progression of premature musculoskeletal decline in this population and discusses preventative measures to reduce the burden of diabetes on the musculoskeletal system.